Yorke Bay, Falkland Islands: a question for coastal management - Bax, Narissa; Bayley, Daniel (Frontiers in ecology and the environment, 2022)
Remote islands, such as those in the sub-Antarctic, represent vitally important oases for coastal megafauna and harbor abundant wildlife. The Falkland Islands are one such biodiversity hub and host a wealth of globally important breeding and foraging locations for animals of higher trophic levels, including gentoo penguins (Pygoscelis papua). Before the COVID pandemic, approximately 60,000 tourists visited the islands annually. Even so, Yorke Bay has for years functioned as a de facto protected area due to the presence of unexploded landmines.